Meta-analysis and systematic review of gout prevalence in the heart/lung transplantation population - Chui, Benedict; Day, Richard; Umashankar, Eshwar; Abdel Shaheed, Christina; Keogh, Anne; Girgis, Laila; Penglase, Ross (Frontiers in Transplantation, 2024)
Introduction Gout may complicate solid organ transplantation with potentially serious consequences. An accurate prevalence of gout in this population is unknown. Objectives This study aimed to estimate the prevalence of gout in the heart and/or lung transplantation population through a systematic review and meta-analysis. Methods MEDLINE, Embase, PsycINFO, CENTRAL and Cochrane Library (inception to February 2022) were searched for studies that reported the prevalence and/or incidence of gout in heart and/or lung transplant recipients. Two authors extracted outcomes data. Data were pooled using a random effects model. Overall quality of evidence was assessed using GRADE. Primary outcomes were the prevalence of pre- or post-transplant gout expressed as a prevalence rate (95% CI). Secondary outcomes included risk factors for gout, adverse events, and therapeutic complications of gout treatment. Results Ten studies were included. Gout prevalence (PR) was 8% pre-transplant (PR = 0.08; 95% CI: 0.05–0.12; 4 studies n = 651) and 6% post-transplant (PR = 0.06; 95% CI: 0.06–0.06; 10 studies n = 45,298). Post-transplant gout prevalence in heart transplant recipients was almost three times higher than lung transplant recipients (PR = 0.16; 95% CI: 0.13–0.20 vs. PR = 0.06; 95% CI: 0.05–0.06 respectively). Patients with a pre-transplant history of gout had a higher risk of developing post-transplant gout than patients without (RR = 3.61; 95% CI: 2.19–5.95). Factors associated with gout and outcomes for heart and/or lung transplant recipients with gout were comprehensively reviewed from the included studies. Conclusion Gout is highly prevalent in heart and/or lung transplant patients. Pre-transplant gout is predictive of developing symptomatic post-transplant gout. This has significant implications for management of heart/lung transplant patients. Systematic Review Registration https://www.crd.york.ac.uk/, PROSPERO (CRD42020190632).